Examining how digital marketplace adoption and fintech adoption contribute to the sustainability of selected small agribusinesses in Metro Manila: A multiple case study approach - Chan, Angela Dominique G. (Animo Repository, 2022)
The agriculture sector is one of the most important industries in the country, and with the ever-growing digital world, the push for the digitalization of the country’s agriculture sector has been one of the goals of the Department of Agriculture. In actuality, the government agency highlighted the importance of the adoption of digital technologies such as eKadiwa and GCash. With this, the study aimed to examine how the adoption of digital marketplace and FinTech contribute to the sustainability of selected small agribusinesses in Metro Manila. This study has utilized a case study method to evaluate the factors contributing to agribusiness sustainability. Eighteen questions that were adapted from different studies were asked in the interviews with five respondents from selected agribusinesses. All propositions were validated through the analysis of findings. It was observed that all the variables with respect to the adoption of digital marketplace and FinTech contributed to the overall agribusiness sustainability of L. Sanchez Farm. On the other hand, all the variables with respect to the adoption of FinTech contributed to the overall sustainability of Chiqhenmart. For the other agribusinesses, only certain variables of the adoption of digital marketplace and FinTech contributed to the overall sustainability of the agribusinesses.